Produção de mudas e cultivo de abacaxizeiro em condições de campo sob adubação potássica e lâminas de irrigação - Venâncio, Jefferson Bittencourt (2013)
Two experiments were conducted with pineapple. An experiment in the acclimatization phase, evaluated the performance of cultivars of pineapple and the effect of substrates with different proportions and sources of organic material in their composition. The other experiment, phase field, studied the effect of potassium fertilization and irrigation on vegetative growth and mineral nutrition of pineapple 'Vitoria' at different sampling times. In seedling production, performance vegetative cultivars of pineapple and efficiency of the organic substrates were evaluated at 210 days of acclimatization. The experimental design was a randomized complete block design, arranged in a factorial 3 × 5, three pineapple cultivars (Perola, Vitoria and Imperial) and five substrates [ORG: Organoamazon ®, commercial compost, SP: Substrate pattern, composed of soil + sand 1:1 (v / v) SP + E + C: composed of sheep manure + SP + carbonized rice hull (2:1:1 v / v) SP + E: comprising SP + E (3:1 v / v) SP + C: C + comprising SP (3:1 v / v)]. Based on the production of plant dry substrate and considering the best performance, there was Perola cultivar superiority over 'Vitoria'e both were superior to' Imperial '. The ORG has provided the aerial part of the plant, increasing it up to 260% and 115% increments over to root density, compared to the group of substrates with soil. In field experiments, the experimental design was a randomized complete block design, arranged in split-split. The plots consisted of potassium doses (0, 10, 20 and 30 g K2O plant-1), the subplots correspond the irrigation levels (L1 = 134.9, L2 = 267.5, L3 = 446.8; L4 = 558.3, and L5 = 655.2 mm), enaquanto the sub-subplots consisted of sampling periods (120, 195, 270 and 345 days after planting - DAP). The effects of doses of K2O (K) and irrigation (L) were independent from each other, but relied on the sampling times (E) for the variables: number of leaves (NL), stem diameter (DC), the plant height (PH) and root dry mass (RDM). Already, in relation to leaf area (LA) and fresh weight (FW) and dry matter (DM) of leaves significant interaction between K × L × E. Based on plant growth, leaf area (11,133 cm2) and fresh weight (1.450 g plant-1) and dried leaves (180 g plant-1), is recommended for growing pineapple 'Victory' in Latossol savanna, dose of 16.9 g of K2O plant-1 and water supplementation of 558.7 mm by sprinkler irrigation. Foliar P and K did not change with the K2O levels, but a significant reduction in water depth corresponding to 134.9 mm. Foliar N responded to application of K2O in the soil, so curvilinear positive at 120 DAP, but showed a linear decrease from 270 DAP. Irrigation L5 reduced foliar N. The leaf Ca and Mg decreased significantly with doses of K2O to 345 DAP. The extraction of nutrients by the plant was affected by the interaction K × L × E, following the contribution of aboveground biomass and physiological age of the plant.